A Theoretical Analysis of Consumer Behaviour for Voters in Ghana - Glate, Stanley Nelvis; Onojaefe, Darlington Peter; Dzansi, Dennis Yao; Amoakoh, Edmund Owusu (Jurnal Maksipreneur, 2024)
This paper identifies evidence of political marketing and, more specifically, consumer-oriented political marketing to analyse the theories of consumer behaviour and identify evidence of consumer behaviour in marketing in the behaviour of Ghanaian voters. The examination used quantitative research to analyse the relationship between three elements: (1) psychology, (2) personal and (3) social to understand the theory of the relationships between campaign messages and voters’ behaviour. Data were collected through a cross-sectional survey with semi-structured questionnaires administered to 7203 randomly selected respondents from participating political parties and voters in Accra, Ghana. Data received were analysed using descriptive statistics and Structural Equation Modelling (SEM). Findings revealed a statistically significant relationship between the behaviour of voters in Ghana and the campaign messages of political parties. This paper concludes that there are opportunities for political marketing and change in voter behaviour. Still, sufficient attention should be given to the understanding of consumer behaviour theory that recognizes the behavioural dynamic of voters in the design of effective campaign messages that are responsive to voters’ needs.